Uji Aktifitas Antifungi Ekstrak Sarang Lebah Dari Luwu Utara Terhadap Candida albicans - Hartini, Hartini (Bioedukasi: Jurnal Pendidikan Biologi, 2017)
Fungi infection is one of the main causes of health problems in Indonesia. One of them is caused by Candida albicans. To overcome infectious diseases can be done by looking for new alternatives with better antifungal activity. One of them uses hive and forest honey. Hive and forest honey contain many secondary metabolite compounds. The purpose of this research is to know the antifungal activity of methanol extract of honeycomb and forest honey to Candida albicans and to determine the effect of extract concentration on Candida albicans. This research includes the extraction process by maceration method and activity testing done by the method of paper disc diffusion.The results showed that the highest antifungal activity was in the extract of hoive methanol Namely bags of pollen, egg bags, honey bags and propolis each having inhibitory power of 20 mm, 19.08 mm, 18.5 mm, 15.7 mm And the lowest antifungal activity was found in the honey methanol extract of 10.1 mm. The higher the concentration of extract, the more the active substance content in it, so the antifungal activity will be greater.